Auriculotherapy for lower urinary tract symptoms in older men: a 4-week, randomised controlled pilot study. (October 2016) - Suen, Lorna; Hon, Wai; Yeung, Kai Wang; Yeh, Chao Hsing; Wong, Hon Fat
Abstract: Background: Lower urinary tract symptoms, which commonly occur among older men, include urinary retention, voiding difficulty, frequent feeling of urinary urgency, and nocturia. Auriculotherapy, a Chinese medicine approach, is a therapeutic method in which specific points in the auricle are stimulated to achieve specific therapeutic purposes. This randomised controlled pilot study aimed to determine whether magneto-auriculotherapy alone or in combination with laser auriculotherapy is more effective than placebo for symptom relief and enhancement of quality of life. Methods: Men aged at least 60 years with an International Prostate Symptom Score of 12 or greater (moderate to severe) were recruited from a residential home in Zhengzhou province, China. We recruited 40 men and randomly allocated to three groups decided by computer-generated randomised table: Group 1, combined auriculotherapy (laser auriculotherapy followed by magneto-auriculotherapy on six auricular points, N=14); Group 2, magneto-auriculotherapy only (placebo laser auriculotherapy followed by magneto-auriculotherapy, N=13); and control (placebo laser auriculotherapy followed by placebo magneto-auriculotherapy, N=13). To achieve the effect of evaluator blinding, another researcher who did not know the type of treatment modality received by the participants evaluated the treatment effect. Treatment was done on one ear at a time. The experimental objects were replaced every second day. Participants were assessed at baseline and after completion of the four-week treatment course. Outcome measures included International Prostate Symptom Score (IPSS); Quality of life due to urinary symptoms (0=delighted to 6=terrible); maximum urinary flow rate (Qmax per second); post-void residual urine test (mL); and Pittsburgh sleep quality index. This trial is registered atClinicalTrials.gov, numberNCT02330107 Ethical approval was obtained from the Human Research Ethics Review Committee, The Hong Kong Polytechnic University. Findings: The mean age of participants was 74·90 years [SD 6·30], with a mean duration of lower urinary tract symptoms of 4·89 years [SD 5·08]. In Group 1, improvements were seen from baseline in lower urinary tract symptoms (mean 20·50 [SD 7·44] vs 13·08 [8·28], p=0·028), quality of life (4·64 [0·50] vs 3·17 [1·53], p=0·016), post-void residual urine (190·43 [117·20] vs 106·75 [79·72] mL, p=0·019) and sleep quality (7·86 [4·58] vs 2·92 [2·58], p=0·009). For patients in Group 2, significant improvement was noted from baseline in lower urinary tract symptoms (20·54 [7·86] vs 13·92 [6·76], p=0·007), quality of life (4·38 [1·19] vs 3·46 [1·33], p=0·01), and sleep quality (mean 8·46 [2·93] vs 5·08 [2·96]). Although patients in the control group also reported improvement in lower urinary tract symptoms (26·08 [8·14] vs 19·00 [8·29], p=0·003) and sleep quality (mean 7·38 [4·79] vs 4·75 [4·09], p=0·008), no significant differences were found for quality of life (4·54 [0·66] vs 4·42 [0·79], p=0·739) or post-void residual urine (157·08 [90·98] vs 158·33 [124·08] mL, p=0·583). We found no effect on Qmax in any group. No adverse events were reported. Interpretation: Magneto-auriculotherapy alone or in combination with laser auriculotherapy can improve lower urinary tract symptoms, quality of life, and sleep quality in men aged 60 years or older with lower urinary tract symptoms. Future studies with a larger sample size could be done to investigate a causal relationship between treatment and effect. Funding: Block Grant 1-ZVD4, School of Nursing, The Hong Kong Polytechnic University, Hong Kong, China.